2017
DOI: 10.1007/s11102-017-0799-5
|View full text |Cite
|
Sign up to set email alerts
|

Sellar and clival plasmacytomas: case series of 5 patients with systematic review of 65 published cases

Abstract: Purpose Parasellar plasmacytomas are rare tumors localized to the sellar region arising from plasma cells. Knowledge of clinical, imaging, surgical, and pathological characteristics is limited to single case reports. Methods A retrospective analysis of 5 primary cases was conducted, followed by systematic review of English language articles using PubMed in accordance with PRISMA guidelines. Results Five primary case patients include four men and one woman, ages 60–77, followed up to three years. A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 61 publications
1
34
1
Order By: Relevance
“…Data regarding the anterior pituitary function in patients with sellar plasmacytomas are not always reported, but it is usually well preserved ( 3 , 5 , 6 , 7 , 8 , 9 ), unlike our case. Lee and coworkers ( 6 ) present 1 patient with hypogonadotrophic hypogonadism and 1 patient with hyperprolactinemia, without hypopituitarism. In their review, they mention 38% (of 26 patients with reported prolactin levels) with hyperprolactinemia and 15% (of 33 patients with reported endocrine evaluation) with hypopituitarism (including their own).…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Data regarding the anterior pituitary function in patients with sellar plasmacytomas are not always reported, but it is usually well preserved ( 3 , 5 , 6 , 7 , 8 , 9 ), unlike our case. Lee and coworkers ( 6 ) present 1 patient with hypogonadotrophic hypogonadism and 1 patient with hyperprolactinemia, without hypopituitarism. In their review, they mention 38% (of 26 patients with reported prolactin levels) with hyperprolactinemia and 15% (of 33 patients with reported endocrine evaluation) with hypopituitarism (including their own).…”
Section: Discussioncontrasting
confidence: 57%
“…There are less than a hundred known cases. Lee and coworkers ( 6 ) performed a recent review of 70 cases of sellar and parasellar plasmacytomas (including 5 new cases reported by the authors). Another 11 different cases have also been included by Joukhadar and coworkers in their previous review ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations